Predicting the extent to which excess lipid is deposited in the physical components of a broiler when dietary protein content is reduced - Reis, Matheus P. [UNESP]; Sakomura, Nilva K. [UNESP]; Azevedo, Jefferson M. [UNESP]; Viana, Gabriel S.; Dorigam, Juliano Cesar P.; Fernandes, Joao Batista K. [UNESP]; Gous, Robert M. (Csiro Publishing, 2022)
Context The weight of each of the physical parts of the body of broilers, predicted using their allometric relationship with feather-free body protein, differs with the level of dietary protein offered.Aims The objective of this study was to account for the excess lipid that is deposited differentially in the physical parts of the body of broilers when dietary protein content is decreased.Methods In total, 2496 day-old Cobb 500 (R) and Ross 308 (R) broilers, equally divided between males and females, were used in a 56-day feeding trial. The experimental design used was a response experiment with six balanced protein concentrations (0.60, 0.70, 0.85, 1.00, 1.15 and 1.30 of the recommendation), with two factors (males and females) and two strains (Cobb and Ross). On Days 14, 28, 42 and 56 post-hatch, eight broilers from each feed x sex x strain combination were euthanised and partitioned into breast, legs, wings, and remainder. Each component was weighed and subsequentially analysed for water, protein and lipid. Allometric equations between the component weights and body protein weight were fitted to describe the responses.Key results In the allometric equations used to describe the additional weight of each component, at a given body protein weight, resulting from the additional amount of lipid that is deposited in the component as a result of reducing the dietary protein content, only the constant terms were affected. By expressing these constant terms as a proportional increase above the genetically determined level of fatness, described by males on the highest dietary protein feed, equations were derived that described the rate of increase in lipid weight with a change in dietary protein content.Conclusions When predicting the weights of different components in the body by using the allometric relationships between the component weight and body protein weight, equations are now available to correct the weights of the respective components of broilers for the additional amount of lipid that would be deposited as a result of feeding dietary protein contents below that required to achieve the genetically desired level of fatness in each component.Implications With the equations presented herein, one can predict the weights of commercial broiler parts, considering the extra fat deposited due to the dietary balanced protein offered, which may lead to decisions that increase the economic return of poultry production.
Keywords: allometry; body composition; chicken; commercial cuts; growth; partitioning of lipid; partitioning of protein; poultry